Factors associated with HPV vaccination initiation among United States college students - Lane McLendon; Jesse Puckett; Chelsea Green; Jenna James; Katharine J. Head; Hee Yun Lee; Jennifer Young Pierce; Mark Beasley; Casey L. Daniel (Taylor & Francis Group, 2021)
Human papillomavirus (HPV) remains the most common sexually transmitted infection (STI) in the U.S. despite widespread availability of a safe, effective vaccine. Although young adults are at greatest risk of HPV infection, extensive vaccine promotion and intervention efforts has been directed toward 11-12-year-olds. College students represent an ideal audience for HPV vaccine "catch-up;" however, research indicates inconsistent HPV vaccination rates within this demographic. An online survey assessing HPV and HPV vaccine knowledge and behaviors was distributed to all undergraduate college students at a large, public university in the Deep South region of the U.S. The primary outcome was receipt of HPV vaccination (binary response options of Yes/No). Logistic regression analyses were performed to determine predictors of HPV vaccination. Of the 1,725 who completed the survey, 47.0% reported having received at least one dose of HPV vaccine; overall series completion (series = 3 doses for this population) was 17.4%. The primary outcome was HPV initiation among college students, defined as having received at least one dose of the HPV vaccine. Results indicated substantial gaps in participants' knowledge of their vaccination status. Provider and parental recommendations as well as social influences were shown to significantly impact student vaccination status, emphasizing the importance of incorporating these elements in future interventions, potentially as multi-level strategies. Future college interventions should address HPV and vaccination knowledge and the importance of provider and parental recommendations.